Taylor Callahan, circuit rider [large type] - Johnstone, William W.; Johnstone, J. A. (Taylor Callahan, Circuit Rider, 2022)
In his younger days, Taylor Callahan didn't know right from wrong - and didn't much care either. As a Confederate bushwhacker, renegade outlaw, and all-around hellraiser, he gave the devil himself a run for his money. Most folks figured Taylor would end up swinging from a noose or shot dead in a poker game. But somewhere along the road to perdition, he decided to change his wicked ways, and fight the good fight against the evil that men do. So he became a traveling preacher. Callahan is no ordinary preacher. He rides the western circuit looking to help lost souls. But his mission of peace takes a violent turn when he enters the godforsaken town of Falstaff, Texas. Better known to locals as "False Hope," this one-time paradise has become a purgatory for homesteaders - thanks to a greedy rancher, corrupt mayor, and notorious confidence man.